Assessing the impact of integrated nutrition education within life sciences on eating behavior among school- aged Moroccan adolescents: A study of construct validity for a measurement instrument - Ech-Chaouy, Abdelhakim; Bouchefra, Said; Rahmaoui, Mehdi; Khal-Layoun, Soad; Bour, Abdellatif (Edelweiss Applied Science and Technology, 2025)
The study aimed to create and validate a test to assess the impact of integrated nutrition education in life science courses on the behavior of Moroccan school-aged adolescents, based on situational judgment test theory. The development process involved reviewing the middle school life science curriculum, conducting semi-structured interviews with educational inspectors and nutritionists, establishing a concordance panel, and carrying out a preliminary study with 378 participants from the second and third years of middle school before the main study. The test demonstrated strong internal consistency (α = 0.89, p < 0.05), suggesting its reliability and validity. Data analysis showed that participant scores followed a normal distribution (p = 0.2) and exhibited significant variation based on school grade (p = 0.001). Within the test dimensions, "diet control" and "food selection" showed significant correlations (Pearson coefficients of 0.67 and 0.66, respectively). In contrast, "food preferences" and "health, diet, and well-being" displayed weaker correlations (0.46 and 0.43, respectively). The review provides valuable insights that educators and policymakers can use to assess and improve existing nutrition education initiatives. The test contributes to enhancing nutrition education, promoting healthy eating, and preventing obesity and diabetes by identifying the strengths and weaknesses of the educational approach, leading to more informed policies.